Prevalence of harmful health misconceptions among elementary school teachers in Claveria and Sanchez Mira districts division of Cagayan II - Agtuca, Cleopatra Planta (1975)
The prevalence of harmful health misconceptions among the elementary classroom teachers in two districts of Cagayan II, Claveria and Sanchez Mira was investigated in this study. These prevailing harmful health practices were identified, how they influence the health practices of classroom teachers investigated and lastly, their implications to health education were derived.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: Elementary school teachers -- Cagayan; Health education -- Cagayan